The quest for global monetary policy coordination - Franco Bruni; José Siaba Serrate; Antonio Villafranca (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
This paper puts forward a proposal to help monetary policies confront the challenge of the 'normalisation' of money creation and interest rates. The difficult unwinding of years of unorthodox policies put financial stability at risk in major monetary centres and in EMEs. The authors argue that global coordination is crucial to facing this challenge. They propose to convene appropriate official meetings to coordinate in an explicit, formal, and well-communicated way the process of normalisation and the discussions on the needed long-term changes in the strategy and institutional setting of monetary policies.
Keywords: E51; E58; E61; E63; F33; F42; 330; monetary policy; central banks; global cooperation; financial stability; international institutions